Acts Against Civil Law Versus Acts Against Criminal Law Versus Rechtsvinding HogeRaad / Supreme Judge - Fernando, Youngky (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
An unlawful act in Dutch is called